Between Transcendence and Immanence: The Construction of Fazlur Rahman's Thoughts about God - Amril Amril; Endrika Widdia Putri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This article analyzes the construction of Fazlur Rahman's thoughts about God. This qualitative research uses Friedrich Schleimacher's hermeneutic method (1764-1834). This study finds that in the construction of Fazlur Rahman's thought, God is One and the First. God is not a dimension, but He is the creator of the dimensions. The existence of God can be found with Himself because He is the evidence for all things. For this reason, everything created by God has a (teleological) purpose, namely as proof of His functional existence. God is transcendent and immanent. Transcendent God implies that God is completely different from all His material creatures. At the same time, the immanent God is